Avaliação de desempenho mecânico e de durabilidade em concretos produzidos com resíduo de beneficiamento de rochas ornamentais tratado termicamente (RBROTT) - Degen, Maxwell Klein (2017)
Worldwide production of ornamental stones in 2014 was 136.5 million tons. Whereas about 25% of blocks are transformed into waste due to processing, it is estimated that approximately 35 million tons of waste were produced. Characterized as a non-reactive material, the dimension stone processing waste (DSPW) acts as filler in cementitious matrix. Nevertheless, after heat treatment at 1200ºC, it becomes a vitreous material, that finely ground presents characteristics of a pozzolanic material. Thus, the heat-treated dimension stone processing waste (HTDSPW) becomes reactive, combining itself chemically with hydrated compounds in the cement paste. With the goal of evaluating the durability properties in high-performance concretes, concretes with 10, 15 and 20% addition of HTDSPW to the cement mass and concretes partially replacing cement by HTDSPW in 10, 15 and 20% were produced. It was assessed the influence of HTDSPW in workability, compressive strength, water absorption and protection against reinforcement corrosion. The HTDSPW use was efficient in the addition as well as in the cement replacement, improving compressive strength in 46%, reducing absorption in 39% and increasing protection against corrosion in up to 90%. The concrete with the best performance was with the addition of 20% of HTDSPW and replacement of 20%.